TINJAUAN LITERATUR SISTEMATIS TENTANG PERUNDUNGAN DI SEKOLAH DASAR: POLA, PENYEBAB, DAN INTERVENSI PENCEGAHAN - Puspitasari, Wiwin; Hitta Alfi Muhimmah; Mochammad Nursalim; Nurul Istiq'faroh; Budi Purwoko (AL IBTIDAIYAH: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study aims to systematically examine the phenomenon of bullying in primary schools, focusing on its patterns, causes, and preventive interventions. Bullying in primary education is a serious issue that can affect students’ social,emotional, and academic development. The study employs a systematic literature review (SLR) approach on 20 scientific articles published between 2019 and 2023, selected from reputable academic databases. Thematic analysis using a descriptive-qualitative approach was conducted to identify key trends and findings related to bullying. The results reveal that verbal and social bullying are the most frequently occurring patterns atthe primary schoollevel. Major causes include low emotional literacy, insufficient teacher and school supervision, andn negative influences from family and community environments. Effective interventions are those involving collaborative efforts among schools, families, and communities. In conclusion, bullying prevention in primary schools requires comprehensive and collaborative strategies that address not only the perpetrators and victims but also the broader educational environment.